Direct N‐Glycofunctionalization of Amides with Glycosyl Trichloroacetimidate by Thiourea/Halogen Bond Donor Co‐Catalysis. Issue 14 (5th March 2018) - Kobayashi, Yusuke; Nakatsuji, Yuya; Li, Shanji; Tsuzuki, Seiji; Takemoto, Yoshiji
Abstract: Using a halogen bond (XB) donor and Schreiner's thiourea as cooperative catalysts, various amides, including the asparagine residues of several peptides, were directly coupled with glycosyl trichloroacetimidates to give unique N‐acylorthoamides in good yields. Synthetic applications of N‐acylorthoamides, including rearrangement to the corresponding β‐N‐glycoside, were also demonstrated. Abstract : Transformation of amides : Using a halogen bond (XB) donor and Schreiner's thiourea as cooperative catalysts, various amides were directly coupled with glycosyl trichloroacetimidates to give unique N ‐acylorthoamides in good yields. Synthetic applications of N ‐acylorthoamides, including rearrangement to the corresponding β‐ N ‐glycosides, were also demonstrated.